2014
DOI: 10.11646/phytotaxa.177.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Botanical advances in Southwestern Amazonia: The flora of Acre (Brazil) five years after the first Catalogue

Abstract: Even though it is well known that the flora of Amazonia is severely under-documented, botanical research in the region has been stagnant for the past two decades or more. An exception to this trend has been the international collaboration in the state of Acre, Brazil. The objective of this study was to assess botanical progress in Southwestern Amazonia, specifically the evolution of our knowledge of the flora of the state of Acre five years after production of the first catalogue of its flora. Between 2006-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 16 publications
1
29
0
3
Order By: Relevance
“…Our results indicate that despite an apparent increase in the rate of growth of the collections, coupled with increased awareness of the need for additional collections in the North and Northeast (e.g. Sobral and Stehmann 2009;Medeiros et al 2014;Moro et al 2014) there has been little or no change in the proportions of the collections deposited in the major regions of Brazil over the past decade or more (Tab. 2).…”
Section: Sampling Sufficiencymentioning
confidence: 75%
See 2 more Smart Citations
“…Our results indicate that despite an apparent increase in the rate of growth of the collections, coupled with increased awareness of the need for additional collections in the North and Northeast (e.g. Sobral and Stehmann 2009;Medeiros et al 2014;Moro et al 2014) there has been little or no change in the proportions of the collections deposited in the major regions of Brazil over the past decade or more (Tab. 2).…”
Section: Sampling Sufficiencymentioning
confidence: 75%
“…The fact is that many of those who have the knowledge and experience to produce authoritative, high-quality taxonomic treatments for the Flora at the pace and scale required to meet the 2020 Target may also be considering the potential impact of this commitment on their career prospects. The ageing profile of the taxonomic specialists willing to tackle large groups has been noted by Medeiros et al (2014) who also reported a shortage of younger taxonomists willing to take their places. Increased availability of data in digital form coupled with user-friendly interfaces to streamline the preparation of species treatments may lighten the burden of the task for taxonomists but it may prove equally important to ensure that the importance of their contributions to science and conservation in Brazil are recognised at the highest level and that this recognition is incorporated into the systems and metrics by which scientists are evaluated and rewarded.…”
Section: Taxonomic Capacitymentioning
confidence: 93%
See 1 more Smart Citation
“…New records were also highlighted by catalogues, such as Zuloaga et al (2008) and Jørgensen et al (2014), floras and monographs (i.e. Medeiros et al 2014).…”
Section: Discussion Overallmentioning
confidence: 99%
“…The list of plants from the Catalogue of the Flora of Acre (Daly & Silveira 2009) was one of the databases added to the system when it was created, and this was reflected in a modest increase of species for this state (7.7%), while dramatic adjustments to the number of endemic species for the state were made between 2010 and 2015, with a fall in the number of endemic species of the order of -46.3%. The recent growth of knowledge regarding the flora of Acre is described by Medeiros et al (2014). Also in the process of organizing its Catalogue, the state of Rio de Janeiro (Baumgratz et al 2014) saw moderate growth in the species number (586 species, growth of 8.7%) and a fall on the number of endemic species (105 species, decreasing -8.9%).…”
Section: Brazilian Geopolitical Divisionsregions and Statesmentioning
confidence: 99%